Pengaruh Penggunaan Project Based Learning Terhadap Motivasi Belajar Siswa Kelas XI Pada Mata Pelajaran Ekonomi Di SMAN 15 Muaro Jambi - Elfonda, Elfonda; Sari, Pratiwi Indah (Universitas Batanghari Jambi, 2024)
This research aims to find out the differences in the influence of using project based learning models and conventional learning methods on the learning motivation of class XI students in economics subjects at SMAN 15 Muaro Jambi. The research design that will be carried out in this research is quasi-experimental research with a quantitative approach. The research results show that there are differences in the use of project based learning models and conventional learning models. The influence of student learning motivation using the project based learning learning model is better than the influence of student learning motivation using conventional learning models even though they both have a good motivational influence on learning.